Inhibition of Poxvirus Replication by Streptovaricin - Quintrell, Nancy A. (1970)
A component of streptovaricin complex inhibits the replication of poxvirus. To be effective, the inhibitor must be introduced early in the replication cycle; it appears to inhibit early messenger ribonucleic acid synthesis by viral cores, thus interfering with all subsequent events. Neither of the two major components of the complex, streptovaricin A or C, was the active component.